Virtual Da’wa Communication between Ustad Yazid Jawas and Ustad Abdul Somad on YouTube - Jihan Afri Batubara; Rubino Rubino; Winda Kustiawan (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This article analyzes the language style of preaching by a senior and well-known preacher in Indonesia, Ustad Yazid bin Abdul Qodir Jawas and Ustad Abdul Somad, on the social media Youtube. The language style for delivering his da'wah was examined for its suitability with the principles of Islamic communication using a sociology of communication approach. This article is a sociolinguistic approach—data analysis techniques with data coding. Samples taken were 18 da'wah videos uploaded by the Youtube account. There were 18 video samples taken from him, as many as 82 expressions/statements, which became the object of research. The results showed that the da'wa language style was quite varied, and the most dominant was satire, 39.02%. As for the suitability of dawah's language style with the principles of Islamic communication, it was found that 53.61% were following the principles of Islamic communication, and 46.38% were outside the principles of Islamic communication.